Geochemical and mineralogical features of the substrates of the Vasyugan Mire, Western Siberia, Russia; Catena; Vol. 194 - Rudmin M. A. Maksim Andreevich; Uilson (Vilson) M. J. Michael Jeffrey; Wilson L.; Savichev O. G. Oleg Gennadievich; Yakich T. Yu. Tamara Yurievna; Shaldybin M. V. Mikhail Viktorovich; Ruban A. S. Aleksey Sergeevich; Tabakaev R. B. Roman Borisovich; Ibraeva K. T. Kanipa Talgatovna; Mazurov A. K. Aleksey Karpovich (2020, 2020)
Title screen